The Relationship between Intimacy Change and Passion: A Dyadic Diary Study - Aykutoğlu, Bülent; Uysal, Ahmet (Frontiers in Psychology, 2017)
In the current study we investigated the association between intimacy and passion by testing whether increases in intimacy generates passion (Baumeister & Bratslavsky, 1999). Furthermore, we examined whether there are partner effects in intimacy change and passion link. Couples (N = 75) participated in a 14-day long diary study. Dyadic multilevel analyses with residualized intimacy change scores showed that both actors’ and partners’ intimacy change positively predicted actor’s passion. However, analyses also showed that residualized passion change scores positively predicted intimacy. Although these findings provide some empirical evidence for the intimacy change model, in line with the previous research (Rubin & Campbell, 2012), they also suggest that it is not possible to discern whether intimacy increment generates passion or passion increment generates intimacy.